2006
DOI: 10.1007/bf03027378
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow in Alzheimer’s disease: Comparison between short and long-term donepezil therapy

Abstract: Relative rCBF significantly increased in the short-term donepezil therapy, while following the long-term therapy, rCBF decreased to the pre-treatment level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Among such AD patients, while some may have remained stable, others may have transiently responded to donepezil therapy, with the cognitive level returning at 24 weeks after the start of donepezil therapy. Furthermore, in terms of the long-term (1 year) effects of donepezil, several previous studies [7,9,10] have reported a difference in the rCBF patterns between the stable and nonstable groups. Unfortunately, under our study design, we could not predict either the very short-or long-term effects of donepezil therapy in AD patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Among such AD patients, while some may have remained stable, others may have transiently responded to donepezil therapy, with the cognitive level returning at 24 weeks after the start of donepezil therapy. Furthermore, in terms of the long-term (1 year) effects of donepezil, several previous studies [7,9,10] have reported a difference in the rCBF patterns between the stable and nonstable groups. Unfortunately, under our study design, we could not predict either the very short-or long-term effects of donepezil therapy in AD patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, a recent study by Yoshida et al [8] reported that clinical improvement as assessed by ADAS-cog with donepezil therapy was the greatest after 3 months' therapy; they also suggested that after 3 months the clinical effect gradually decreased to the pretreatment level. Several SPECT studies have demonstrated significant increases in the rCBF of the frontal lobe after 1 month's [8] or 3 months' [7] donepezil treatment. Therefore, the rCBF in areas containing cholinergic neuronal pathways may increase during the early stages of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fi nding of cerebral hypoperfusion in the bilateral posterior cingulate gyri, precunei, and inferior parietal cortex of the brain using positron emission tomography (PET) and single-photon emission computed tomography (SPECT), and the application of statistical images have been established as early diagnostic tools of AD [6][7][8][9][10]. The effectiveness of the SPECT response to drug treatment and diagnosis at the stage prior to clinical diagnosis of AD have also been reported [1,11,12]. Matsuda 1 3 interest (VOI) in the posterior cingulate gyri, precunei, and inferior parietal cortex using easy Z score imaging system (eZIS) and developed a program (specifi c VOI analysis) that automatically fi gured out the following indicators: severity, extent, and ratio [13].…”
Section: Introductionmentioning
confidence: 99%